Numerical Simulation of the Inlet/Outlet Pressure Ratio Effect on the Heat Transfer Coefficient in an Air Turbine Cascade - He, Z.; Lin, J.H.; Sun, X.Y.; Gu, X. (Проблемы прочности, 2019)
Based on the state-of-the art methods of gas turbine cascade heat transfer assessment, a theoretical model of the two-dimensional air turbine cascade is proposed, wherein gas flows past the turbine blade profile. The velocity, temperature, and pressure fields, as well as the heat transfer distribution along the pressure and suction surfaces, the leading and trailing edges of the turbine blade were computed via FLUENT software at different pressure ratios. This permitted of studying the heat transfer evolution at different pressure ratios in the same position and at the same pressure ratio in different positions. На основе разработанных методов оценки теплопередачи газовой ступени турбины предложенатеоретическая модель двухмерной ступени аэротурбины, в которой газ течет мимо контура лопасти турбины. Поля скоростей, температур и давлений, а также распределениекоэффициента теплопередачи вдоль поверхностей давления и разрежения, передней и задней кромок лопасти турбины рассчитывались с помощью программы FLUENT при разном отношении давлений. Это позволило исследовать эволюцию коэффициента теплопередачи при различном отношении давлений в одинаковом положении и при одинаковом отношении давлений в различных положениях. На основі розроблених методів оцінки теплопередачі газової ступені турбіни запропонована теоретична модель двомірної ступені аеротурбіни, в якій газ тече повз контуру лопаті турбіни. Поля швидкостей, температур і тисків, а також розподіл коефіцієнта теплопередачі вздовж поверхонь тиску і розрідження, передній і задній крайок лопаті турбіни розраховувалися за допомогою програми FLUENT при різному співвідношення тисків. Це дало змогу дослідити еволюцію коефіцієнта теплопередачі при різному ставленні тисків в однаковому становищі і при однаковому ставленні тисків в різних положеннях.